A Death Audit of H1N1 Influenza Cases in a Tertiary Care Hospital in Southern Rajasthan (Current Out Break - 2017) - Ashish Jain; Rupa Sharma; Mukesh Kumar Nagar; Pratap Bhan Kaushik (Medsci Publications, 2018)
Background: Swine flu deaths are preventable, Clinico- epidemiological profile of the H1N1 infected patients varies with place and time. Death audit unravels the circumstances that lead   to these avoidable deaths and help save other patients. The study was conducted to identify clinico-epidemiological profile of the H1N1 confirmed deaths, to know the Onset-to-hospitalization (OH) time, hospitalization to death time and pre hospitalization management by other health care providers. .Methods: Death audit of H1N1 positive cases was done at RNT Medical College, Udaipur during the outbreak from July'17 to De- cember'17. Results: Deaths were higher in 20 years to 40 years age group, male:female = 1.1:1. Overall fatality was 6.6%. Majority (52.5%) re- ported with breathlessness, fever and cough. Only five received oseltamivir within 48 hours, 95% had Anemia and Diabetes. 26.3% females were pregnant. Mean OH time was 5.8 days ± 2.81. 60 % died within 72 hours of hospitalization Conclusion: Mortality was high in adult, male:female =1.1:1. Most had reported after 48 hours with severe illness and co-morbid conditions and had not received Oseltamivir. Most deaths oc- curred within 72 hours of hospitalization.